Animal and plant factors which affect larkspur toxicosis in cattle: Sex, age, breed, and plant chemotype. (July 2019) - Green, Benedict T.; Keele, John W.; Bennett, Gary L.; Gardner, Dale R.; Stonecipher, Clint A.; Cook, Daniel; Pfister, James A.
Abstract: Larkspur ( Delphinium spp . ) poisoning is a long-term problem for cattle grazing on rangelands of western North America. Recent research has shown that both plant and animal-based factors are critical in understanding and mitigating larkspur poisoning in cattle. Non-toxicological factors including sex, age, cattle breed, and plant chemotype affect cattle responses to larkspur. For example, Angus heifers are more susceptible to larkspur intoxication than are steers or bulls. Young cattle appear to be more susceptible to larkspur poisoning than mature animals. Beef breeds of cattle are more susceptible to larkspur intoxication than dairy breeds. In addition to animal factors, plant alkaloid composition (chemotype) affects the potential toxicity for cattle because of differences in the ratios and concentrations of highly toxic N -(methylsuccinimido) anthranoyllycoctonine (MSAL)-type alkaloids compared to less lethal non-MSAL-type alkaloids. Animal- and plant-based factors can provide substantial information to inform livestock producers on management to reduce risk and cattle losses to various larkspur species in western North America. Highlights: Larkspurs ( Delphinium spp . ) are a significant problem for cattle grazing on rangelands of western North America. Cattle age, breed, and sex are important factors in the physiological response to larkspur toxins. Larkspur plant alkaloid composition (chemotype) also affects the intoxication of cattle.